2017
DOI: 10.17140/tcoj-2-108
|View full text |Cite
|
Sign up to set email alerts
|

Topical Corticosteroid Misuse Among Females Attending a Dermatology Outpatient Department in Ethiopia

Abstract: Introduction: Irrational use of topical corticosteroid (TC) is quite common in Ethiopia due to the unrestricted availability and use of topical steroids (TS) not only by general public but also by physicians and chemists. This practice is highly prevalent and sought after, owing to the quick relief of symptoms in different dermatological conditions and its nature of enhancing beauty for a certain period. Objective: This study aims to evaluate and analyze the prevalence of misuse of topical steroids, causes beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Trong đó: n là cỡ mẫu; Z với mong muốn mức tin cậy là 95% thì Z 1− α 2 = 1,96; p=26,4% (tỷ lệ nhiễm nấm dermatophytes trên FCAD dựa theo nghiên cứu của Zewdu và cộng sự năm 2017) [11]; d là sai số cho phép trong nghiên cứu là 7%, d=0,07. Vậy n=153.…”
Section: Phương Pháp Nghiên Cứuunclassified
See 1 more Smart Citation
“…Trong đó: n là cỡ mẫu; Z với mong muốn mức tin cậy là 95% thì Z 1− α 2 = 1,96; p=26,4% (tỷ lệ nhiễm nấm dermatophytes trên FCAD dựa theo nghiên cứu của Zewdu và cộng sự năm 2017) [11]; d là sai số cho phép trong nghiên cứu là 7%, d=0,07. Vậy n=153.…”
Section: Phương Pháp Nghiên Cứuunclassified
“…Tỷ lệ nhiễm nấm da dermatophytes trên bệnh nhân viêm da do lệ thuộc corticosteroid ở mặt là 19,6%. Theo nghiên cứu của Zewdu và cộng sự (2017) cũng ghi nhận tỷ lệ nhiễm nấm trên bệnh nhân FCAD cao hơn một ít là 26,4%, thấp hơn kết quả nghiên cứu của Meena và cộng sự (2017) là 49,46% và cao hơn rất nhiều so với nghiên cứu của Sarawat và cộng sự (2011) là 6,7% và của Chauhan và cộng sự (2019) là 4,97% [3], [4], [8], [11]. Sự khác biệt về mặt tỷ lệ nhiễm nấm da có thể là thời tiết, khí hậu và độ ẩm từng mùa ở các nước có sự khác nhau, trong đó miền Nam nước ta có khí hậu ẩm, nóng là một yếu tố thuận lợi cho nấm dermatophytes phát triển.…”
Section: Bàn Luậnunclassified
“… 1 - 3 Studies conducted in India, Nepal, Saudi Arabia, and Ethiopia have reported a considerable burden of irrational use of topical corticosteroids and fairness creams to lighten the skin tone. 4 - 6 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Studies conducted in India, Nepal, Saudi Arabia, and Ethiopia have reported a considerable burden of irrational use of topical corticosteroids and fairness creams to lighten the skin tone. [4][5][6] The irrational use of topical corticosteroids and fairness creams may lead to many serious adverse effects on the skin including acne, skin atrophy, striae, rosacea, perioral dermatitis, acne, and purpura. [7][8][9]…”
mentioning
confidence: 99%